426 EFFECTS OF DISRUPTING C-MET ACTIVITY WITHIN PANCREATIC CANCER. (1st January 2005) - Patel, B. K.; Warner, S.; Haiyong, H.
Abstract : Pancreatic cancer is the fourth or fifth leading cause of cancer death in the Western world. Human pancreatic cancers frequently overexpress human epidermal growth factor receptors including Met, also known as hepatocyte growth factor receptor. Over stimulation of c-Met via its natural ligand, hepatocyte growth factor (HGF), has been associated with cell scattering, angiogenesis, enhanced cell motility, invasion and eventually metastasis. The overexpression of c-Met was confirmed by western blot and RT-PCR in a panel of human pancreatic cancer cell lines. The results from this expression analysis suggested there is an over activation of the c-Met signaling pathway, which may contribute to pancreatic cancer growth and metastasis. This hypothesis was tested using a cell-based invasion assay through which the invasive effects of c-Met signaling in pancreatic tumorigenesis was evaluated. Preliminary results indicate a two-fold increase of invasion in those CF-Pac1 cells treated with HGF. In addition to providing information regarding the role that c-Met and HGF play in tumorigenesis, this work further validates c-Met as a therapeutic target for the treatment of pancreatic cancer and other tumor types.